Effect of soil amendment on early growth of Vitex pubescens stumps - Kusmina, S.; Budhi, S.; Sriwardani, F.; Utama, R.; Rantan, D.; Jong, W. de (1998)
This study demonstrated that the P3 treatmnet, with 1 volume of green charcoal per 5 volumes of soil, produces the best results for growing Vitex pubescens planting stock. Under this treatment, the medium reaches pH (H2O) of 7.04 and pH (KCI) of 6.75, the greatest number of shoots develop, these shoots have the largest length increment, and the greatest number of leaves develop. This leads to the conclusion that one volume of green charcoal mixed with five volumes of the soil available locally in possible production sites for Vitex pubescens is a suitable medium for the production of planting stock (Kusmina 1997). Treatment P1 (1:1) resulted in the largest increase of roots, but this had no significant influence on sprouting of shoots, length increment, or diameter increment of these shoots, or the number of leaves. It appears that the nutrient supply reached toxic levels under this treatment (Setyamidjaja 1986)